2019
DOI: 10.1371/journal.pone.0218114
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient nickel (II) removal by sewage sludge biochar supported α-Fe2O3 and α-FeOOH: Sorption characteristics and mechanisms

Abstract: A novel approach was employed to load α-Fe 2 O 3 and α-FeOOH onto sewage sludge biochar (SBC) with the purpose of efficient nickel (Ni) removal. A high Ni(II) adsorption capacity of 35.50 mg·g -1 in 100 ppm Ni(II) solution with 10 mg modified sewage sludge biochar (MSBC) was achieved. The adsorption kinetic and isotherm were fitted well by the pseudo-second-order model and the Langmuir model, respectively. The optimal pH was found around a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 48 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…However, the heavy-metal-adsorption capacity of sludge-based biochar is unsatisfactory, which limits its promotion and application to a certain extent [42, 43]. Some modifiers such as Fe 3 O 4 [44], nanostructured CaCO 3 [45], trithiocyanuric acid trisodium salt [46], α -Fe 2 O 3 and α -FeOOH [47], K 2 FeO 4 [48], and hydroxyapatite [42] have been successfully applied to prepare modified sewage sludge biochar, and satisfactory heavy-metal-adsorption capacity has been achieved. At present, chemical modification is a noteworthy research direction for improving the adsorption capacity of heavy metals by sewage sludge biochar [45, 49].…”
Section: Introductionmentioning
confidence: 99%
“…However, the heavy-metal-adsorption capacity of sludge-based biochar is unsatisfactory, which limits its promotion and application to a certain extent [42, 43]. Some modifiers such as Fe 3 O 4 [44], nanostructured CaCO 3 [45], trithiocyanuric acid trisodium salt [46], α -Fe 2 O 3 and α -FeOOH [47], K 2 FeO 4 [48], and hydroxyapatite [42] have been successfully applied to prepare modified sewage sludge biochar, and satisfactory heavy-metal-adsorption capacity has been achieved. At present, chemical modification is a noteworthy research direction for improving the adsorption capacity of heavy metals by sewage sludge biochar [45, 49].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that KOH activation produced biochar with a superior Pb(II) adsorption capacity (57.48 mg/g) than other examined biochar. For effective nickel (Ni) removal, Yang reported in his study (Yang et al, 2019) used a unique method to load 𝛼-Fe 2 O 3 and 𝛼-FeOOH onto SSB.…”
Section: According To the Study The Surface Of The Ssb Precipitates B...mentioning
confidence: 99%
“…The results showed that KOH activation produced biochar with a superior Pb(II) adsorption capacity (57.48 mg/g) than other examined biochar. For effective nickel (Ni) removal, Yang reported in his study (Yang et al., 2019) used a unique method to load α$\alpha $‐Fe 2 O 3 and α$\alpha $‐FeOOH onto SSB. With 10 mg of modified SSB, a solution containing 100 ppm of Ni(II) was able to obtain a high Ni(II) adsorption capacity of 35.50 mg/g.…”
Section: Industrial Applications For Environmental Remediationmentioning
confidence: 99%
“…Furthermore, FeOOH was believed to react with Fe 0 to generate Fe 3 O 4 due to no FeOOH being found in this study. Meanwhile, it has been demonstrated that Fe(OH) 3 can produce the mixture of FeOOH and α-Fe 2 O 3 at the range of 40-80 • C (Equation (15)) [63,64]. FeOOH could be converted to Fe 2 O 3 due to poor chemical stability (Equation (16)) [63].…”
Section: Optimization Of Removal Processmentioning
confidence: 99%